A Survey of PJKR UIBU Students' Interest in Pursuing a Teaching Career After Participating in “Kampus Mengajar Program” - Adhi, Febri Hernowo; Istiawan, Nurcholis (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aimed to examine the career interests of PJKR students at Universitas Insan Budi Utomo after they participated in the Kampus Mengajar program. Using a descriptive quantitative approach, data were collected from 30 respondents through a 9-item questionnaire that covered affective, cognitive, and conative dimensions. The data analysis revealed that 57% of students had a high interest level, 33% had a very high interest level, and 10% had a moderate interest level. Additionally, item-level analysis revealed strong emotional engagement: 96.6% felt proud helping students, and 93.4% enjoyed teaching. Cognitively, 90% understood teacher responsibilities, and 86.7% felt confident in PJOK teaching methods. Conative responses were slightly lower; 83.3% intended to join PPG, and 86.6% planned to apply as PJOK teachers. While affective and cognitive dimensions were highly positive, a slight dip in commitment-related items suggests varying levels of certainty in long-term career plans. These findings highlight the positive impact of experiential learning in fostering teaching interest, especially in physical education.